2020
DOI: 10.1016/j.maturitas.2020.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Are we equal in adversity? Does Covid-19 affect women and men differently?

Abstract: Background & objectives: This article examines whether women are less prone than men to Covid-19 infections and their complications. Data sources: We reviewed available databases and searched systematically for publications. To be taken into account, data had to be broken down by gender. There was no study evaluation nor quantification synthesis, due to the large heterogeneity of the studies. Nineteen databases were selected. 73 publications were considered and 33 were selected, to which 12 more were added. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
77
2
20

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 45 publications
8
77
2
20
Order By: Relevance
“…Preliminary studies have suggested that the sex of an individual is a factor associated with the risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and the severity of the disease [128][129][130]. De Lusignan et al, [128] found that the male sex is associated with an increased risk of SARS-CoV-2 infection.…”
Section: Coronavirus Disease 2019 (Covid-19) In Relation To Sex-a Lacmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary studies have suggested that the sex of an individual is a factor associated with the risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and the severity of the disease [128][129][130]. De Lusignan et al, [128] found that the male sex is associated with an increased risk of SARS-CoV-2 infection.…”
Section: Coronavirus Disease 2019 (Covid-19) In Relation To Sex-a Lacmentioning
confidence: 99%
“…De Lusignan et al, [128] found that the male sex is associated with an increased risk of SARS-CoV-2 infection. Additionally, males often develop a more severe form of coronavirus disease 2019 (COVID-19) and are more likely to die from the disease compared with females [129,130]. Dangis et al, [131] drew a computed tomography (CT)-based association between the male sex and extensive lung disease, independently of age and time of symptoms onset.…”
Section: Coronavirus Disease 2019 (Covid-19) In Relation To Sex-a Lacmentioning
confidence: 99%
“…Throughout Europe, 73% of admissions to ICUs were men. Deaths were more common among men than among women in all countries except India and Pakistan [7].…”
Section: Introductionmentioning
confidence: 98%
“…The authors concluded that men and women had a similar incidence of the diseases, but that men with COVID-19 or SARS-CoV-1 infection were at higher risk of worse outcomes and death, independent of age [6]. A review of 48 articles representing multiple countries and databases confirmed this finding [7], reporting that males accounted for 55-62% of hospitalized patients. The sex imbalance was even more pronounced for admissions to intensive care units (ICUs), with a male proportion of 65-74%.…”
Section: Introductionmentioning
confidence: 99%
“…Os homens apresentaram maior proporção de óbitos por COVID-19, cerca de 56,4% a mais que as mulheres, mesmo estas apresentando idade média superior aos homens. Outros estudos também têm apontado maior ocorrência do evento nesse grupo, que acompanham, também, as tendências brasileiras para o mesmo período 7,8 .…”
Section: Discussionunclassified